Outcome of pregnancies with spontaneous PPROM before 24 + 0 weeks' gestation. (August 2016) - Wagner, Philipp; Sonek, Jiri; Mayr, Stefanie; Abele, Harald; Goelz, Rangmar; Hoopmann, Markus; Kagan, Karl Oliver
Abstract: Objective: To examine the contemporary outcome in women with rupture of membranes (PPROM) before 24 + 0 weeks' gestation. Study design: Retrospective analysis of women with spontaneous PPROM before 24 + 0 weeks that were treated at the University of Tuebingen/Germany. The search of the database included common maternal and pregnancy characteristics as well as the neonatal outcomes. Results: One hundred and one pregnancies fulfilled the inclusion criteria. 32 (31.7%) women opted for termination of pregnancy, which were excluded from further analysis. The gestational age at PPROM in the 69 women with an expectant management was 21.3 (IQR 19.1–22.6) weeks. 40 (58.0%) pregnancies carried on beyond 24 + 0 weeks. Multiple regression analysis indicated that the time of PPROM and the absence of oligo-/anhydramnios were associated with a prolongation beyond 24 + 0 weeks. In the 40 pregnancies that remained intact beyond 24 + 0 weeks' gestation, the fetuses were born at 27.7 (IQR 25.3–30.9) weeks. Survival without major complications was observed in 22 (55.0%) fetuses. Multiple regression analysis indicated that only the gestational age at the time of delivery was significantly associated with such an intact survival. Conclusion: In cases with PPROM there is a 60% chance of a prolongation beyond 24 + 0 weeks. About half of these fetuses will be discharged alive without major complications.